Motivating Power System Protection Course Students by Practical and Computer-Based Activities - Shahnia, Farhad; Moghbel, Moayed; Yengejeh, H. (IEEE, 2015)
This paper presents several methods for motivating students taking a power system protection (PSP) course. The paper reviews the laboratory activities developed for the PSP course at Curtin University, Australia; these methods are applicable and can be used for PSP course instruction at any institution. These activities were developed to improve the learning experience of the electrical engineering undergraduate and postgraduate students enrolled in this course. Initially, the PSP course at Curtin University consisted of lectures and tutorials accompanied by two sessions of software-based simulations and one session of laboratory demonstration. To motivate the students, several computer-based simulations and practical laboratory experiments were developed. PSCAD and ETAP power system analysis software tools are introduced and used to demonstrate the performance and coordination of different protection relays from steady-state and dynamic points of view. Also, a practical setup composed of a LabVolt power system simulator and industrial relays is used to carry out several practical experiments. The experiments help students observe the performance of protection systems for transformers and induction motors during faults and abnormal operating conditions. Finally, the concept of relay testing and commissioning is introduced by relay standalone experiments using a secondary injection relay test set. The results of these activities were evaluated according to the students’ satisfaction, comments, total scores, and interest in PSP.